Time deals: optimization of lag - Timofey Yu. Shabanov (Овощи России, 2019)
Relevance. In many ways, a successful purchase and sale transaction is determined by the time it takes to complete it. The search for the best deal time is linked to the optimization of the time lag. The purpose of the study is to optimize the time lag of the agricultural market.Methods. This article considered a role of time in business processes for Russian potato market of producer into period 1998-2018.Results. There was trend of annual reduction about 365 thousand tons (1.2...1.7% of total) per year supply of potatoes on Russian domestic market of producers. Some priority of quantity vs price of producer been revealed. There was inverse proportional function between producers` prices and quantity of potatoes. That is than worse harvest that higher producer`s price. Reducing a supply of potatoes 1 million tons from agricultural market perhaps increase in producer prices by $ 8.5 / t (4...5% on average). Offered concept and hypothesis about linearization of equilibrium of market processes into conditions of time shifts of dynamics their parameters were confirmed. There verified assumption about existence of inter-interval time optimum which this linearization maximal business processes. In course of correlation analysis of dynamics of annual indicators of potato market, it revealed month May of current period as optimal time of producer's offers with price restrictions and diminishing returns, and month September with quantity restrictions and increasing returns. If fixation of producer`s prices situation of deals May more likely, in case of crop failure (limited quantity) in September.